Analysis of Leadership Style, Organizational Culture, and Organizational Commitment on Employee Performance Moderated by Reward System - Pahotan, Jones; Wibowo Widhianto, Chandra (Journal of World Science, 2023)
Employee performance has a very important role in the success of a company. Employees who have good performance will help the company achieve its goals and vision, but not all have good performance; some employees only meet sufficient criteria, as happened with the employees of RM SME Regional Office Jakarta 1 PT. Plat Merah Berwarna Biru Bank. This research aims to analyze the role of reward system variables in moderating the influence of leadership style, organizational Culture, and organizational commitment on employee performance. This research is categorized as causality research with a quantitative approach. The sample was determined using a simple random sampling technique. Research data was collected by distributing questionnaires to 145 samples. Data analysis was carried out using the partial least squares method through the SmartPLS version 3 program. The research results show that each variable of leadership style, organizational culture, organizational commitment, and reward system directly has a significant effect on employee performance. The reward system can only moderate the influence of organizational culture on employee performance, but the reward system has yet to moderate the influence of leadership style and organizational commitment on employee performance.